Potential Aquatic Medicinal Plants in Jaffna District and Its Conservation Strategy - Kokilan, K.; Sathiyaseelan, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2016)
Aquatic plants are plants that have adopted to live in aquatic environment. They are found mostly in pools, ponds, lakes, streams, rivers. Sri Lanka is the smallest country but rich in diversity. The aim of the study is to identify the aquatic medicinal plants for its sustainable use. The plants of aquatic ecosystems played fascinating role in the life of human beings in earlier days as food, fodder and medicine. Aquatic region in Jaffna district are identified with the help of map and the places are visited and the aquatic medicinal plants are identified and recorded. Accordingly 25 aquifers had been visited for the last 2 years and 16 aquatic medicinal plants have been identified. Among the aquatic Medicinal plants 6 of them has refrigerant pharmaceutical action. One can be used for DM, two for rejuvenating, five for skin, three for CVS, two for GIT, two for CNS and one for locomotor system. Due to the dryness and loss of rain, these plants are in endanger to destruction, more than this some ponds are nurtured and some vanished in order to build building and sewage mix with some ponds this cause the destruction of aquatic habitat. Awareness and absence of knowledge about aquatic medicinal plants also pave way for the destruction. Therefore the aquatic medicinal plants are identified in Jaffna in order to prevent their destruction and to conserve them for future.
Keywords: Aquatic medicinal plants; Aquifers; Conservation; Medicinal uses